Ultrastructural changes in epithelial cells of rats exposed to low concentration of hydrogen sulfide for 50 days. (1st November 2016) - Yalçın Yeler, Defne; Aydın, Murat; Hocaoğlu, Peyami Turgay; Koraltan, Melike; Özdemir, Hakan; Kotil, Tuğba; Gül, Mehmet
ABSTRACT: Hydrogen sulfide (H2 S) and other volatile sulfur compounds (VSCs) appear mainly in the oral air of patients with halitosis. It seems that VSCs are directly involved in the pathogenesis of gingival diseases. In previous studies, short-term (7 hours–4 days), high concentrations (5–400 ppm) of H2 S applications on periodontal tissues have been evaluated in a culture medium. The aim of the present study was to investigate the potential effects of lower (equivalent to halitosis) concentrations of H2 S on rat gingival tissue for longer-term inhalation. The threshold level of pathologic halitosis perceived by humans at 250 ppb of H2 S was converted to rat equivalent concentration (4.15 ppm). Rats in the experimental (H2 S) group (n=8) were exposed to H2 S continuously but not the control rats (n=8). After 50 days, the gingival sulcular tissue samples of each rat were taken and examined using transmission electron microscope. Ultrastructural changes in the sulcular epithelia of the rat gingiva showed deformation of celullar shape, vacuolization, and disintegrity of intercelullar connection by loss of desmosomes and collagen fibrils. No basal membrane damage was observed. Inhalation of low levels of H2 S (equivalent of halitosis) in the oral environment causes ultrastructural celullar damages in rat sulcular mucosa. These results suggest that halitosis may be the potential reason for periodontal destruction in humans.